Digestion of epithelial tissue of the rumen wall by adherent bacteria in infused and conventionally fed sheep. - Dinsdale, D (1980)
Comparisons were made, by light and electron microscopy, of the rumen epithelium of sheep fed conventionally and fed by infusion of volatile fatty acids and buffer into the rumen and casein into the abomasum. Similar bacterial colonization of the epithelium was observed in each case. The mitotic index of epithelial cells in infused sheep was high, as it was in barley-fed animals, while the mitotic index of cells from animals receiving roughage was low. The bacterial flora appeared to be actively digesting the epithelial cells. The fate of sloughed epithelial cells in the rumen fluid of sheep fed by infusion was also studied. The sloughed cells were rapidly digested, probably by their attached flora of facultatively anaerobic, highly proteolytic bacteria, leaving abundant highly keratinized remnants in rumen fluid. The importance of epithelial cell turnover and of proteolysis by partially facultative bacteria in the rumen is discussed.